ANALYSIS OF PISTON PUMP FLOW INVESTIGATION - Іващенко, Василь Трифонович; Лях, Михайло Михайлович; Концур, Іван Федорович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Piston pump flow investigations are given in the article. Relationships for defining of nonuniformity degree and factors of single and double – acting pumps flow were obtained. Analysis of overflow factor calculation, that determine quantity characteristic of nonuniformity flow and pulsation pressure damper parameters were conducted. Flash flow of all kind acting pumps of different constructive features and angle lag open-close operation of valves were investigated. Constructive scheme for pulsation flow reducing and increasing its efficiency was suggested.